Many Body Interactions and Lattice Dynamics of Gold - Thapa, S.R.B. (Himalayan Physics, 2011)
Lattice dynamics of gold is studied theoretically using phenomenological model. This model considers (i ion-ion and (ii) ionelectron interactions to evaluate the potential energy. Contribution to ion-ion interaction is the sum of two body central interactions between ions and many body interactions among ions. Contribution to potential energy due to ion-electron interactions is evaluated using screened coulomb potential. Using this model phonon frequencies of gold are computed at 48 non-equivalent points of Brillouin zones of crystal and compared with experimental points. Lattice specific heats at different temperatures are evaluated by dividing the frequency spectrum in interval of 0.1 tiga hertz. Using the computed values of lattice specific heats, Debye characteristic temperatures of gold are computed. The model is used to calculate compressibility and Poission's ratio. Agreement of theoretical calculations with experimental results is satisfactory. Key words: Ion-ion interaction; Ion-electron interaction; Phonon frequency; Lattice specific heat; Debye characteristic temperature The Himalayan Physics Vol.1, No.1, May, 2010 Page: 44-47 Uploaded Date: 28 July, 2011